Survey of Hospital Drains Antibiotic Resistant Bacteria for Hygiene and Health Care - Makky, Essam A. (2012)
The antimicrobial susceptibility of twelve bacterial isolates obtained from different three hospital drains in Cairo, Egypt isolated within three months was determined, using agar diffusion method. Only twelve out of twenty-eight antibiotic resistant bacterial isolates were selected according to their sensitivity for equal or more than two antibiotics used. Isolates from hospital drains were subjected to antimicrobial susceptibility testing and the percent of resistance bacteria were subjected to thirteen antibiotics as the following: CN (58.3%), CAZ (91.7%), CTX (91.7%), TOB (83.3%), CEP (83.3%), IPM (25.0%), SXT (33.3%), VA (75.0%), AK (25.0%), SAM (58.3%), FEP (50.0%), CIP (8.3%), and CRO (75.0%). The relationship between plasmid and antibiotic resistant bacteria explained from pharmaceutical products isolates and detected two plasmids while isolates from hospital drains detected also two plasmids and one isolate detected four plasmids.